2014
DOI: 10.1179/1351000214y.0000000113
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-based anticancer activity of a novel synthetic analogue of capsaicin, capsaicin epoxide

Abstract: Our data indicate that the antiproliferative activity of capsaicin epoxide is potentiated in vitro, when used at much lower concentrations compared with capsaicin at similar concentrations. Thus, the findings of this study may have implications for phytochemical-based anticancer drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
2
24
3
Order By: Relevance
“…As a positive control of apoptosis induction, cells were treated for 30 min with 10 mM hydrogen peroxide (HP) [18]. UA- and BA-mediated changes in mitochondrial membrane potential were evaluated using Muse™ Cell Analyzer and Muse™ Mitopotential Assay Kit (Merck Millipore) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…As a positive control of apoptosis induction, cells were treated for 30 min with 10 mM hydrogen peroxide (HP) [18]. UA- and BA-mediated changes in mitochondrial membrane potential were evaluated using Muse™ Cell Analyzer and Muse™ Mitopotential Assay Kit (Merck Millipore) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Capsaicin may induce the death of human lung and prostate cancer cells through DNA and chromosomal damage while the capsaicin epoxide is a better antiproliferative agent according to Lewinska et al 36,37 On the other hand, dihydrocapsaicin was found active against the human colon and breast cancer cells. 38 Two other main compounds found in chili peppers, the reduced ascorbate and dehydroascorbate, are cofactors in hydroxylation reactions and play an important antioxidant role in the body.…”
Section: Pure Capsaicin Vs Extractmentioning
confidence: 99%
“…Most remarkably, the growthsuppressive activity of RPF151 is independent of the TRPV1 receptor. Lewinska et al (2015) synthesized a constrained capsaicin analog that contained an epoxide motif in Region C of the capsaicin (Fig. 6C).…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 99%
“…6C). The growth-suppressive activity of capsaicin epoxide (CE) compared with capsaicin was studied in a diverse array of cell lines using the MTT assay (Lewinska et al, 2015). Both capsaicin and CE did not reduce the viability of human dermal fibroblasts.…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 99%